Penerapan aplikasi bank sampah berbasis deskstop - Subandi, Subandi (Borneo Novelty Publishing, 2025)
The implementation of the Kenanga 36 Waste Bank application has become part of the waste processing sector such as waste banks. Apart from being a place to save and sort waste, waste banks also play a role in educating the public about processing waste into items that are useful and have selling value. Even though the service process at the Kenanga 36 Waste Bank is still manual by recording in books, this results in a lack of accuracy and precision. Therefore, a computerized system is needed to improve the performance and development of waste bank institutions. To overcome this problem, the author has designed a system for transactions and savings management at the Kenanga 36 Sampah Bank. The results of this Sampah Bank application are expected to speed up and make it easier for Sampah Bank officers to carry out transactions and manage customer savings data.